TEXTUAL ANALYSIS ON CELEBRITY NEWS IN THE ONLINE MEDIA - Degaf, Agwin; Wijana, I Dewa Putu; Poedjosoedarmo, Soepomo (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2019)
This research examines online media related to the cases of Indonesian celebrities using critical discourse analysis approach. It aims to explain the textual strategies used by online media upon reporting the cases. The textual strategy focuses on the selection of certain vocabulary and the use of specific grammar. The data are collected through reading and note taking techniques on news texts in the online media, liputan6.com and kapanlagi.com, with certain topics such as: the divorce of Marshanda, Asmirandah interfaith marriage, and the case of celebrity prostitution. The current descriptive qualitative research employs critical discourse analysis proposed by van Dijk which generally believes that media always contains interests and partisanships. Therefore, they tend to provide positive picture of themselves/groups (positive self-presentation) and negative images about others (negative other-presentation).The picture can be analyzed through the way the media use the diction and build certain sentences inside the news. The result shows that media uses the vocabulary such as mothers who have an affair, women who cannot be emulated, presumptuous women, a liar man, no longer Muslim, etc. when reporting on the case of Marshanda’s divorce and Asmirandah’s interfaith marriage. Furthermore, the researcher finds the use of passivation, abstraction, categorization, identification and anonymity strategies in grammar.